Implementasi Bimbingan Belajar Olimpiade dalam Mencetak Siswa Berprestasi Pada Mata Pelajaran PAI di Sekolah - Irawan, Wahyudi Saputra; Khoiriyah, Khoiriyah; Sholihin, Imam; Himawan, Fajaruddin; Husain, Athar (Jurnal Multidisiplin Ibrahimy, 2026)
The implementation of tutoring for Olympiad material is an effective strategy in improving student achievement in Islamic Religious Education (PAI) subjects in schools. This study aims to analyze the process of implementing Olympiad tutoring and its impact on improving student achievement. The research method uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that Olympiad tutoring can improve learning motivation, conceptual understanding, and students' analytical skills, thus producing high-achieving students in the field of PAI. The implementation of BPMO tutoring in producing high-achieving students in PAI subjects, the Role of BPMO Tutoring in Producing High-Achieving Students in PAI Subjects.